Comparative transcriptome analysis of different tissues of Hylomecon japonica provides new insights into the biosynthesis pathway of triterpenoid saponins - He, Bing; Xu, Teng; Xu, Shaowei; Fang, Huqiang; Yang, Qingshan (Frontiers in Bioinformatics, 2025)
Triterpenoid saponins are one of the main activities of roots and rhizomes of Hylomecon japonica, with various pharmacological activities such as antibacterial, anticancer, and anti-inflammatory. To elucidate the biosynthesis pathway of triterpenoid saponins in H. japonica, DNA nanoball sequencing technology was used to analyze the transcriptome of leaves, roots, and stems of H. japonica. Out of a total of 99,404 unigenes, 78,989 unigenes were annotated by seven major databases; 49 unigenes encoded 11 key enzymes in the biosynthesis pathway of triterpenoid saponins. Nine transcription factors were found to be involved in the metabolism of terpenoids and polyketides in H. japonica and a spatial structure model of squalene synthase in triterpenoid saponin biosynthesis was established. This study greatly enriched the transcriptome data of H. japonica, which is helpful for further analysis of the functions and regulatory mechanisms of key enzymes in the biosynthesis pathway of triterpenoid saponins.